Complete Genome Sequence of a Multidrug-Resistant Acinetobacter baumannii Isolate Obtained from a Mexican Hospital (Sequence Type 422) - Castro-Jaimes, Semiramis (Genome Announc, 2016)
Acinetobacter baumannii has emerged as a dangerous nosocomial pathogen, particularly for severely ill patients in intensive care units and patients with hematologic malignancies. Here, we present the complete genome sequence of a multidrug-resistant A. baumannii isolate, recovered from a Mexican hospital and classified as sequence type 422 according to the multilocus sequence typing Pasteur scheme.